SCENT OF SOFT PROPAGANDA IN NATION BRANDING: TOURISM MARKETING STRATEGIES IN THE “WONDERFUL INDONESIA” CAMPAIGN - Haeruddin, Muhammad Ilham Wardhana; Putra, Muh. Al Fatah Arief; Hardiyanti, Andi Aryani (Universitas Negeri Makassar, 2026)
Abstract: This study critically examines the ideological dimensions of the Wonderful Indonesia campaign as a contemporary manifestation of soft propaganda within the practices of nation branding and tourism marketing. Framed through the lens of Critical Discourse Analysis (CDA) based on Fairclough’s three-dimensional model, this research investigates how visual, linguistic, and symbolic representations operate as instruments of persuasion that construct Indonesia’s national identity within the global tourism arena. Data were collected through multimodal analysis of official campaign materials distributed across digital platforms, including the Ministry of Tourism and Creative Economy’s website, YouTube, Instagram, and TikTok, supported by secondary documents and scholarly sources. The findings reveal that Wonderful Indonesia integrates aesthetic visuals, emotional narratives, and cultural symbolism to portray Indonesia as a harmonious, inclusive, and exotic nation while subtly reinforcing neoliberal and nationalistic ideologies. The campaign functions not only as a promotional initiative but also as a mechanism of symbolic governance where marketing, diplomacy, and ideology converge under the logic of digital capitalism. Furthermore, the study identifies the emergence of participatory propaganda in the digital era, wherein audiences contribute to reproducing state narratives through social media engagement mediated by algorithmic visibility. Theoretically, this study contributes to the critical understanding of nation branding as an ideologically charged practice that negotiates power among the state, market, and media. Practically, it underscores the importance of adopting ethical, reflective, and inclusive communication strategies in national branding ones that balance aesthetic appeal with narrative authenticity and social responsibility.Keywords: Nation Branding, Soft Propaganda, Critical Discourse Analysis, Tourism Marketing, Wonderful Indonesia